Novel Model for Manoeuvrability of Ships Advancing in Landslide-Generated Tsunamis - Peiyin Yuan; Pingyi Wang; Yu Zhao (Advances in Civil Engineering)
The rock and soil on the shore of the bank are unsteady and slide in a poor environment, affecting the water body in the river channel and forming landslide-generated tsunamis. This directly impacts the navigation of vessels in the river. In this study, the river course and sailing ships in the Wanzhou section of the Three Gorges Reservoir area were taken as the research objects. Through a physical model test with a large scale ratio, the variation of the water level at the monitoring points in the channel was determined, and the variation law of the water level in the whole channel was derived and converted into a prototype through the scale ratio. A model of the ship’s manoeuvring motion was established, and the ship’s manoeuvring motion characteristics in still water were verified. The correlations between the maximum roll angle and the navigation position, sailing speed, and rudder angle were investigated in detail. A safety risk response theory of navigation in the area of landslide-generated tsunamis was proposed, and a scientific basis was provided for the safe navigation of ships in the Three Gorges Reservoir area.